فعا لية استخدام التواصل الاجتماعي "تيك توك" لترقية مهارة الكلام لطلاب الفصل العاشر في المدرسة العالية الإسلامية الأهلية "الأشعري" كيراس جومبانج - Yunita, Eka; Qodir, Abdul (JURNAL AL-IHDA : Media Ilmiah Bahasa Arab, 2024)
The technological revolution brought about by innovation has given rise to various types of new media, one of which is the TikTok application. The purpose of using TikTok as an educational medium is that students are expected to be more enthusiastic and active in the learning process, and students can be more confident in speaking Arabic and can develop the speaking skills of tenth grade students of Madrasah Aliyah Al-Asy'ari Keras Jombang. This research method uses a quantitative approach with the One Group Pretest Postest Design method in tenth grade students of Madrasah Aliyah Al-Asy'ari Keras Jombang. The results of this study state that social media "Tik Tok" is one of the easy ways that can help students in learning Arabic and in mastering speaking skills. The data obtained came from the results of the pre test and post test and the results were normal with a value of sig>0.05 and the data was normally distributed with a result value of 141. In conclusion, there is a significant positive impact of using social media "Tiktok" to improve speaking skills. namely the effect of using social media "Tiktok" gets a result of .000 so if the value is sig>0.05 then HA is accepted and HO is rejected.